Retirement Preparation Workshop: Building a Business with Digital Marketing - Rimadias, Santi (PT. Riset Press International, 2025)
Retirement is a transition phase that requires readiness not only from financial aspects, but also mentally and socially. In the midst of rising life expectancy and uncertain economic dynamics, retirement is no longer interpreted as a period of complete quitting of work, but rather as an opportunity to remain productive and economically independent. One of the relevant strategic approaches in preparing for retirement is the development of entrepreneurship based on digital marketing. The Retirement Preparation Workshop designed by PT Edukasindo Utama and Kopindo Consult to equip prospective retirees of PT. Toyota Boshoku Indonesia (TBINA) with business building skills with digital marketing. Through this workshop, participants not only understand how to build a business, but also gain practical skills in utilizing social media and marketplaces as a means of marketing. The results of the workshop are expected to encourage the creation of economic independence among retirees and strengthen their readiness to face the post-work period through the digital entrepreneurship route.